Mongolian Education and Science Vocabulary - Anna V. Mazarchuk (Oriental Studies)
Introduction. The article deals with semantics and etymology of several basic terms of Mongolian culture vocabulary relating to education and science. Goals. The study shall primarily describe how the lexical layer in question was formed, and trace the sources of such borrowings. Materials and methods. The materials were collected from Mongolian-Russian and Mongolian explanatory dictionaries via continuous sampling. The identified lexemes were checked against corresponding entries to Mongolic / Turkic etymological dictionaries and bilingual dictionaries of Sanskrit, Chinese, and Tibetan. Results. Some of the analyzed words happen to have been borrowed into Mongolian from Uighur, but Uighur was not the ultimate source of the lexemes: Mong. шавь ‘disciple, pupil’ < Uig. šabï had come to Uighur from Sanskrit via Chinese; Mong. багш ‘teacher’ < Uig. baqšı and Mong. бичиг ‘writings’ < Uig. bitig are originally Chinese; Mong. ном ‘book’ < Uig. nom had come to Uighur from Greek via Sogdian. Some other words, such as Mong. боловсрол ‘education’, эрдэмтэн ‘scientist’, ухаан ‘intelligence’ (in шинжлэх ухаан ‘science’), оюутан ‘student’ ― have common Turko-Mongolic (bol- ‘become’, uqa- ‘comprehend’) or even common Altaic (ere- ‘male’, oyu- ‘mind’) stems, but their new semantics referring to various phenomena of education and science appeared comparatively recently, to a large extent, as a result of attempts to find new words for the notions introduced by Chinese culture and Uighur Buddhism. The words зүй and судлал, as well as derivatives from the stem sur- belong to common Mongolic lexis. Conclusions. Most of the analyzed words were borrowed into Mongolian from Uighur as part of religious vocabulary. Some of these terms originally derive from Chinese, Sanskrit or even Greek. Indigenous Mongolic lexemes are derivatives from sur- ‘to study’, and the terms зүй ‘theory’ and судлал ‘study’ that are used as parts of science names.